A New Method of Reference Signals Calculation for Switching Compensator - Yiying Wang; Jiangong Liu; Yang Liu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexThe switching compensation devices, such as active power filters and static var generator, are growing rapidly for power quality improvement. The current reference signals is one of the important factor affecting the responsible speed and compensation effect. In this paper, a new strategy for reference signals calculation is present based on Current’s Physical Components. Through the orthogonal decomposition of the load current by the CPC power theory, the reference current, for various compensation objectives of switching compensation devices, can be calculated by the combination of the orthogonal current components. It is demonstrated that this strategy can be used for various compensation goals of limited switching compensation devices and changing the compensation objectives on-line according to the power grids. The validity of the developed strategy is verified by the simulation results.